Upaya Pencegahan Pergaulan Bebas di Lingkungan Remaja SMP Negeri 2 Adonara Timur Kecamatan Witihama - Karmelita Monis Yempormiasse; Kristianus Simon Hale Molan; Indriyati Indriyati; Marianus Kleden; Karolus Tatu Sius; Hendrikus Likusina Kaha; Alfry Aristo J. Sinlae; Yohanes Kornelius Ethelbert; Yasinta Palan Peten; Stephanie Perdana A. Lawalu (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Promiscuity is a form of deviant behavior or crossing the boundaries of prevailing values and norms. Teenagers' responses about preventing promiscuity in the youth environment in Adonara, Witihama District, East Flores Regency need to be developed in students who are still in school. The socialization and education activities carried out at SMP Negeri 2 Adonara Timur aimed to create a healthy community environment and avoid social deviations, namely promiscuity. The method used in this activity is the direct instruction method. To prevent promiscuity, it is important to socialize teenagers about the negative impact of promiscuity. This socialization can be done through an educational approach to teenagers or with a more targeted personal approach. The personal approach has proven to be effective in reducing the prevalence of promiscuity, which is increasing in the current era.